Column adsorption studies on carbazole removal using β-cyclodextrin-functionalized activated rice hull biochar - Rajandran, Prabu; Masngut, Nasratun; Nor Hasmaliana, Abdul Manas; Nur Izyan, Wan Azelee; Siti Fatimah Zaharah, Mohamad Fuzi; Mohamad Abd Hadi, Bunyamin (Elsevier Ltd, 2025)
In recent years, β-cyclodextrin-functionalized activated rice hull biochar (CD-ARHB) has emerged as a promising adsorbent for aromatic compounds, owing to the host–guest interactions facilitated by the hydrophobic cavity of β-cyclodextrin. However, its potential for removing carbazole (CAR), a persistent aromatic pollutant, remains largely unexplored. This study addresses this critical gap by evaluating the effectiveness of CD-ARHB in removing CAR from aqueous environments. For this purpose, CD-ARHB was first synthesized through hydrochloric acid activation of rice hull biochar, followed by β-cyclodextrin functionalization. The resulting material was then characterized using scanning electron microscopy, Fourier-transform infrared spectroscopy, thermogravimetric analyzer, elemental analyzer, and gas sorption analyzer, which confirmed successful activation and functionalization. After characterization, batch adsorption experimental data were modeled to assess the isotherm and kinetic behavior, revealing multilayer adsorption governed by chemisorption. Subsequently, a two-stage optimization process comprising the one-factor-at-a-time method and response surface methodology was employed to maximize the adsorption performance of CD-ARHB for CAR in a continuous adsorption system. Under the optimal conditions of CD-ARHB dosage of 2.7 g, feed flow rate of 1.9 mL/min, and influent CAR dosage of 18 mg/L, CD-ARHB exhibited a remarkable adsorption capacity of 26.37 mg/g. Furthermore, desorption studies using dichloromethane revealed good regeneration potential, with over 50 % of the adsorption capacity retained after three cycles. These findings underscore the efficacy and reusability of CD-ARHB, highlighting its promise for environmental remediation applications.